Heterogeneity in Gender/Sex Sexualities: An Exploration of Gendered Physical and Psychological Traits in Attractions to Women and Men. Issue 8 (13th October 2018) - Schudson, Zach C.; Manley, Melissa H.; Diamond, Lisa M.; van Anders, Sari M.
Abstract : Sexuality research has generally privileged attractions based on partners' sexed physical bodies over attractions based on other features, including gender expression and personality traits. Gender may actually be quite central to sexual attractions. However, its role has received little empirical attention. To explore how gendered and sexed features, among others, are related to sexual attractions, the current study assessed how sexually diverse individuals described their attractions to feminine, masculine, and gender-nonspecific features of women and men. A sample of 280 individuals responded to the open-ended questions: "What do you find attractive in a man?" and "What do you find attractive in a woman?" We coded responses as pertaining to physical and/or psychological features, and as being gendered masculine, feminine, or gender-nonspecific. Our analyses showed that participants named gender-nonspecific features most frequently in responses to both questions, feminine features more than masculine features in attractions to women, and masculine features more than feminine features in attractions to men. Additionally, participants named feminine physical features more than masculine physical features, and masculine psychological features more than feminine psychological features, both in their attractions to women and overall. These results highlight the importance of considering attractions based on gender, rather than sex alone.